Satuan Lingual dalam Pembuatan Batu Bata Merah di Desa Jatilaba Kabupaten Tegal (Kajian Etnolinguistik) - Fikri, Bukhori; Kurnia, Ermi Dyah (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
The objectives of this study are describing the form of the lingual unit, describing the meaning of the lingual unit, and describing the function of the lingual unit in the red bricks manufacture. Data analysis was performed using structural and ethnolinguistic language analysis techniques for the lingual unit used. Based on the results of the analysis, lingual units in the form of words found in the making of red bricks in Jatilaba Village, Tegal Regency are basic words, derived words, and compound words. In addition to that, there are lingual units in the form of phrases classified according to the distribution, core categories, and lingual units of the elements. The meaning of the lingual unit in the red bricks manufacture in Jatilaba Village, Tegal Regency is analyzed based on its lexical and cultural meanings. The lexical meaning of the lingual unit is divided based on several meanings, namely, based on tools, material, activities, and results of activities. The lingual unit function found is as a communication tool, as a link to the supernatural world, as a form of utilization of natural resources, indicating the origin of the process name of the instrument used, indicating the origin of the process name from the sound produced, indicating the origin of the process name from the results obtained, utilizing technology, describing the technique of making true red bricks, and as hereditary teachings. Keywords: lingual unit, meaning, ethnolinguistics, and function.